Economic incentives and comparative advantage in Indonesian food crop production - Gonzales, Leonardo A.; Kasryno, Faisal; Perez, Nicostrato D.; Rosegrant, Mark W. (International Food Policy Research Institute, 1993)
In Indonesia production of food crops grew an impressive 4.3 percent a year between 1978 and 1988, largely as a result of favorable government pricing, research, and investment policies toward rice and other crops. In recent years, however, the high costs of subsidies to the government and the increasing competition for scarce resources among commodities have caused Indonesian policymakers to take a fresh look at these policies in order to determine what is needed in a changing economic environment. What policies should the government pursue for rice and other major food crops? Should the government provide incentives or investments to promote rice as an export crop? What have been the effects of government policies on the international competitiveness of other commodities such as corn or cassava? Is there a continuing role for large input subsidies, or should these subsidies be eliminated? What investments are appropriate in the food crop sector? The report examines trends in the government policies and production of five major food crops (rice, corn, soybeans, sugar, and cassava) in Indonesia; analyzes the effects of government input-output pricing policies on domestic production incentives for these food crops; and assesses their relative comparative advantage under the three trade regimes of import substitution, interregional trade, and export promotion.